Photothermal therapy with silver nanoplates in HeLa cells studied by in situ fluorescence microscopy - Rivas Aiello, María Belén (2021)
Photothermal therapy (PTT) is a noninvasive treatment for cancer relying on the incorporation of NIR-light absorbing nanomaterials into cells, which upon illumination release heat causing thermally induced cell death. We prove that irradiation of aqueous suspensions of poly(vinylpyrrolidone)-coated silver nanoplates (PVPAgNP) or PVPAgNP in HeLa cells with red or NIR lasers causes a sizeable photothermal effect, which in cells can be visualized with the temperature sensing fluorophore Rhodamine B (RhB) using spinning disk confocal fluorescence microscopy or fluorescence lifetime imaging. Upon red-light irradiation of cells that were incubated with both, RhB and PVPAgNP at concentrations with no adverse effects on cell viability, a substantial heat release is detected. Initiation of cell death by photothermal effect is observed by positive signals of fluorescent markers for early and late apoptosis. Surprisingly, a new nanomaterial-assisted cell killing mode is operating when PVPAgNP-loaded HeLa cells are excited with moderate powers of fs-pulsed NIR light. Small roundish areas are generated with bright and fast (<1 ns) decaying emission, which expand fast and destroy the whole cell in seconds. This characteristic emission is assigned to efficient optical breakdown initiation around the strongly absorbing PVPAgNP leading to plasma formation that spreads fast through the cell.